The Ulama, Thought-styles, and the Islamic State Debate in Contemporary Malaysia - Norshahril Saat (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2014)
During the 1980s Islamic resurgence in Malaysia, the Pan-Malaysian Islamic Party (PAS) championed the formation of an Islamic state, while the ruling United Malays National Organization (UMNO) retained its Malay/nationalist and secular ideology. However, in the run up to the 2008 general elections, PAS revealed its manifesto as Negara Berkebajikan Malaysia, or ‘benevolent’ state, and retained it for the 2013 elections. Conversely, some quarters within UMNO called for the implementation of shariah law. Has PAS become more moderate than UMNO? This article discusses the common threads underlying both parties’ views of the Islamic state. By examining the personal writings, publications, and religious sermons of the dominant ulama (religious scholars) of both parties, this study seeks to illuminate their attitudes towards Islam in general, and towards the idea of Islamic state in particular.DOI: 10.15408/sdi.v21i1.878